A model of competing gangs in networks - Alexis Poindron; Nizar Allouch (Games, 2024)
Two groups produce a network good perceived by a third party, such as a police or military institution, as a 'public bad', referred to as 'crime' for simplicity. These two groups, considered mafias, are assumed to be antagonists, whether they are enemies or competitors in the same market, causing harm to each other's activities. This paper provides guidelines for the policymaker, typically the police, seeking to minimize overall crime levels by internalizing these negative externalities. One specific question is investigated: the allocation of resources for the police. In general, we recommend a balanced crackdown on both antagonists, but an imbalance in group sizes may lead the police to focus on the more criminal group.
Keywords: D19; D74; D79; 330; crime; networks; strategic complementarity; strategic substitutability